Household Adoption of Technology: The Case of High-Speed Broadband Adoption in Australia. (May 2017) - Adams, Peter; Farrell, Mark; Dalgarno, Barney; Oczkowski, Edward
Abstract: Within the home context a high-speed broadband Internet connection is seen as a key enabler for effective access to and use of the Internet. This article examines the factors contributing to household adoption of high speed broadband in Australia. Building on the Theory of Reasoned Action and seminal research on technology adoption in the home and the workplace, the article presents and evaluates a hypothesized model of Household Adoption of Technology. Highlights: Investigates innovation adoption, identifying a new key factor influencing household intention to adopt high-speed broadband. Lifestyle compatibility, perceived affordability, purchase complexity (new) and social influence are significant in adoption. Questions whether the TAM model is suitable for predicting behavioural intention in the household context and extends MATH.